(untitled) (Scientific journal of the Fergana State University, 2023)
The article draws on the analysis of the symbolic meaning, in particular, the image of a crane, expressed through birds in an artistic work. The ideological-aesthetic content of the creators, who applied to the image of the crane through different genres, was studied with the help of this detail.